An integrative index of Ecosystem Services provision based on remotely sensed data - Paruelo, José María (2016)
We present an approach to generate estimates and to map Ecosystem Services (ES) related to C and water dynamics (Soil Carbon sequestration, evapotranspiration and groundwater recharge) and biodiversity (Avian Richness) from remotely sensed data in two ecoregions of South America: the Semiarid Chaco woodlands and the Rio de la Plata grasslands. Two attributes of the seasonal dynamics of the Normalized Difference Vegetation Index (NDVI); the annual mean (NDVI mean), an indicator of light interception and hence of total C gains and the intra-annual Coefficient of Variation of the NDVI (NDVI CV), a descriptor of seasonality; were combined into an ES provision index (ESPI = NDVImean * (1-NDVICV)). The proportion of the variance in ES provision explained by the ESPI varied from 0.484 for avian richness up to 0.662 for C sequestration. A relatively large proportion of the studied area presented changes in ES provision. A 32,4% of the Semiarid Chaco and the Rio de la Plata grasslands presented significant (p < 0.01) trends. Most of the trends (30.2%) were negative, showing a decrease in ESPI. An index like the one proposed here can be used as an aggregated indicator of the status and/or trends of ES supply at large spatial scales (subcontinental in our case).